Factors Influencing Community Participation in Sustainable Beef Cattle Waste Management in Kediri City, Indonesia - Muarof, Alven; Azizah, Siti; Wahju Nursita, Ita (CV. Komunitas Dunia Peternakan, 2025)
Farmers in Kediri City still have low awareness of proper livestock waste management. It has also been reported that many local residents have complained about the pollution caused by livestock waste. Furthermore, the waste is often disposed of in makeshift dumping sites created by the farmers themselves, and some farmers even discharge livestock waste into the Brantas River. The purpose of this study was to analyze livestock farmers' participation and the factors influencing their involvement in the livestock waste processing program. The sampling technique in this study used the purposive sampling method, for sampling the population of farmers, it was obtained by the purposive sampling method, namely selecting respondents who participated in the beef cattle waste processing program in Kediri City. The main variables observed in this study were: motivation (X2), perception (X3), role of stakeholders (X4), participation (Y1), and sustainability (Y2). This research study employed a descriptive survey method. The questionnaires are the main tool in gathering data. The data analysis method involved statistical model testing using SEM SmartPLS. The results showed that livestock farmers' participation in the beef cattle waste processing program was influenced by motivation and perception variables. This is attributed to the minimal role played by stakeholders in livestock waste processing in Kediri City. Furthermore, higher levels of motivation and more positive perceptions are associated with greater participation, which in turn has a positive impact on sustainability.